Maeloka Toba’: Studi Kasus Waria Yang Kembali Menjadi Laki-Laki Normal di Kabupaten Soppeng - Safitra, Nur (Emik, 2024)
The controversy of the existence of transgender (waria) is evident. In Soppeng, Their existence has recently become controversial with its various activities, one of which is the Porseni waria event throughout South Sulawesi which resulted in strong protests from the surrounding community because this event is considered as an effort to carry out an indirect campaign in supporting to legalize LGBT, including waria. This was mainly triggered by the increasing number of waria communities. While waria are increasingly and openly proving their existence and their groups in Soppeng, there are also waria who intend and/or are transformed into full men. This article deals with how waria repent in order to return to their biological sex status as normal men. This qualitative research was conducted in Lalabata District of Soppeng Regency for three months in 2023. I triangulate between in-depth interview and observation as my data collection methods. There were eight waria involved in this study whose age between 26 and 46 years, with various types of work (private employees, gold sellers, farmers, waiters and construction workers). The study indicates that there are two main factors that trigger the repentance of waria to be a full male, internal and external factors. The internal factors consist of something stucking in one’s heart, desire to start a new life, desire to get married, and spiritual calling, as the main trigger; the external factors include family encouragement and social pressure, as the supporting trigger. Internal and external factors are intertwined with each other. The repent strategies carried out by waria comprise of staying away from waria social environment, changing appearance, following ruqyah, and attending tarbiyah/taklim/religious lectures. In addition, the impacts of conversion experienced by waria is feeling happy, changing their appearance, and planning their future life by building a family and deepening their religion. It is argued in this article that the further away a waria is from his community, the easier for waria to repent and to transform into a normal man.